Implementation Readiness of RPJPN 2025–2045: Strengthen the Role of Bappenas in Supporting Long‑Term Development Planning - Budi Cahyono; Tjitjik Rahaju; Firre An Suprapto (The Journal of Indonesia Sustainable Development Planning, 2026)
Bappenas readiness plays a central role in supporting the implementation of RPJPN 2025–2045. This study examines institutional readiness by assessing human resource capacity, coordination, regulatory support, data systems, and policy continuity. A mixed-method approach is applied, combining surveys of planners with in-depth interviews. The findings show that planners understand long-term development goals and are able to translate them into annual programs. However, key challenges still remain in coordination between sectors, data integration, and maintaining program continuity across government periods. These gaps limit effective monitoring, reduce program impact, and weaken alignment between planning and implementation. The study highlights the need to strengthen coordination mechanisms, integrate data systems, and align performance evaluation with long-term targets. These improvements are essential not only for Bappenas, but also for strengthening national planning systems and ensuring that long-term development goals can be implemented and benefit the countries in the future.